Foreign Direct Investment in Wartime: Factors, Consequences and Recovery - Hrytsenko, Larysa; Derkach, Liliia; Hedegaard, Michael; Vaarst, Kristina (European Journal of Sustainable Development, 2025)
Geopolitical instability has a substantial impact on foreign direct investment (FDI), increasing investment risks and weakening economic resilience in conflict-affected countries. This study examines the effects of political instability on FDI inflows, focusing on a comparative analysis of two groups of countries characterized by varying degrees of geopolitical stability: (1) politically stable European Union member states (e.g., Germany, France) and (2) conflict-affected economies (e.g., Ukraine, Libya). Utilizing World Bank statistics, the research applies statistical and econometric methods, including correlation analysis, regression analysis and analysis of variance (ANOVA), to examine investment trends and identify the key determinants of FDI under wartime conditions. The results indicate that wartime and conflict-related factors significantly suppress FDI activity, whereas political stability, along with the absence of violence and terrorism, constitutes one of the important factors in restoring investor confidence in conflict-affected settings. In contrast, FDI in politically stable economies appears less sensitive to fluctuations in political stability. The results of this study may assist policymakers and organizations in shaping strategies to support FDI inflows and economic recovery in conflict-affected regions. Keywords: foreign direct investment, war, political stability, geopolitical instability, political risks, economic recovery